2019
DOI: 10.1021/acs.iecr.9b00103
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydroconversion of Oleic Acid into Aviation-Fuel-Range Alkanes over Ultrathin Ni/ZSM-5 Nanosheets

Abstract: Ultrathin Ni/ZSM-5 nanosheet catalysts with different acid concentrations, B/L (Brønsted/Lewis acid sites) ratios, and nanosheet thicknesses are designed for the hydroconversion of oleic acid into aviation-fuel-range alkanes (AFRAs). The role of acid concentration/distribution and nanosheet thickness was investigated. High acid concentration enhances the hydrodeoxygenation (HDO) reaction and intrinsic deoxygenation activity because of the synergistic effect between acid sites and metal sites. The selective cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 58 publications
(94 reference statements)
0
16
0
Order By: Relevance
“…The maximal aviation fuel selectivity of 45% was acquired at 360 °C. However, the selectivity reduced to 31% at elevated temperatures owing to the secondary cracking of C 9 –C 15 alkanes (up to 66%) . PtNi@HS-1 possessed fewer acid sites but with higher catalytic performance compared to the PtNi/S-1 catalyst; the discrepancy in product distribution for these two catalysts is ascribed to the hollow encapsulated structure.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The maximal aviation fuel selectivity of 45% was acquired at 360 °C. However, the selectivity reduced to 31% at elevated temperatures owing to the secondary cracking of C 9 –C 15 alkanes (up to 66%) . PtNi@HS-1 possessed fewer acid sites but with higher catalytic performance compared to the PtNi/S-1 catalyst; the discrepancy in product distribution for these two catalysts is ascribed to the hollow encapsulated structure.…”
Section: Resultsmentioning
confidence: 98%
“…However, the selectivity reduced to 31% at elevated temperatures owing to the secondary cracking of C 9 − C 15 alkanes (up to 66%). 67 PtNi@HS-1 possessed fewer acid sites but with higher catalytic performance compared to the PtNi/S-1 catalyst; the discrepancy in product distribution for these two catalysts is ascribed to the hollow encapsulated structure. Based on the results of FE-TEM, XPS, and ICP− OES, the active metals in the PtNi@HS-1 catalyst are mainly located in the cavities with a shell thickness of around 20 nm.…”
Section: Introductionmentioning
confidence: 93%
“…Py-IR spectra were recorded at a desorption temperature of 200 °C and the results are shown in Figure . The two peaks at around 1454 and 1545 cm –1 were attributed to LASs and BASs, respectively . After the Gaussian function fitting and integration of spectra, the content of LASs and BASs for these samplesis summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The two peaks at around 1454 and 1545 cm −1 were attributed to LASs and BASs, respectively. 37 After the Gaussian function fitting and integration of spectra, the content of LASs and BASs for these samplesis summarized in Table 4. The amount of BASs and LASs of Z was 0.044 and 0.012 mmol g −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The second factor is the catalyst type. It was shown that transition metal catalysts result in HDO or DO processes [14][15][16][17][18][19][20][21][22]. In some studies, DCN was mentioned as an unconventional pathway for fatty acid conversion to hydrocarbons over transition metal catalysts [23,24].…”
Section: Introductionmentioning
confidence: 99%